Twitter, Politics, and the Pandemic - Isidoropaolo Casteltrione (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
This article examines the intersection of politics, government, and health communication in the Scottish Twittersphere during the Covid-19 outbreak. It captures two phases of the pandemic: the beginning of the health crisis, and the rollout of the vaccination programme, coinciding with the emergence of the Delta variant in Scotland. A combination of thematic, quantitative content and social network analyses is employed to identify key themes emerging from the tweets of selected government and politicians' accounts, and to explore the formation of social networks communities. The thematic analysis reveals that Twitter has primarily been used for disseminating information about the virus, preventative measures, and government interventions, with limited efforts towards public engagement. Twitter communications became increasingly partisan as the pandemic progressed, with users frequently using the crisis as a political proxy. Five major clusters were detected in the Twitter network: two highly partisan and polarised clusters; a group containing numerous news media accounts reporting on the pandemic, and two clusters focusing primarily on the vaccination programme and the provision of health information, where the First Minister and the Scottish Government operate. Implications of these findings for government and political communication in health crises are discussed.